2008
DOI: 10.3748/wjg.14.5192
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine anesthesia reduces intestinal ischemia/reperfusion injury in rats

Abstract: showed significantly less injury in rats that received ketamine than in rats that did not (2.35 ± 1.14 vs 4.58 ± 0.50, P < 0.0001). The distance traveled by a marker, expressed as percentage of total intestinal length, in rats that received pentobarbital sodium was 20% ± 2% in comparison with 25.9% ± 1.64% in rats that received ketamine (P = 0.017 INTRODUCTIONMesenteric ischemia is a clinical entity with a mortality rate between 60% and 100% that usually requires surgical resection of the necrotic intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…19 The current study confi rmed those earlier fi ndings, and demonstrated that ketamine acts in a dose-dependent manner. Ischemia/reperfusion injury in the intestine and other tissues is thought to be mediated by the release of proinfl ammatory cytokines, induction of complement, leukocyte activity, increased vascular permeability, and loss of barrier function.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…19 The current study confi rmed those earlier fi ndings, and demonstrated that ketamine acts in a dose-dependent manner. Ischemia/reperfusion injury in the intestine and other tissues is thought to be mediated by the release of proinfl ammatory cytokines, induction of complement, leukocyte activity, increased vascular permeability, and loss of barrier function.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study showed that total ketamine anesthesia reduced intestinal mucosal damage and motility alterations after I/R, in comparison to pentobarbital anesthesia. 19 The current study investigated the effects of pretreatment with various anesthetic and subanesthetic doses of ketamine on intestinal mucosal injury, infl ammatory cell infi ltration, and myenteric plexus neuron morphology.…”
Section: Introductionmentioning
confidence: 99%
“…-/NO 3 -content and dry/wet intestine ratios As shown in Figure 5D and E, NO 2 -/NO 3 -content in serum in I/R group rats was lower than that in the Sham group (P,0.01). 3 -content in serum in I/R group rats (P,0.01).…”
Section: Measurement Of Nomentioning
confidence: 99%
“…3 -content in serum in I/R group rats (P,0.01). Administration of simvastatin/PEG-b-PBLG 50 remarkably increased NO 2 -/NO 3 -content (12.3±0.65 μmol), which was remarkably greater than that in the I/R group (P,0.01); the dry/wet (D/W) intestine ratios in I/R groups rats were lower than those in Sham group (P,0.01). The D/W intestine ratios reached 3.08±0.06 in Sham group, whereas the D/W intestine ratios in I/R groups reached 6.25±0.09.…”
Section: Measurement Of Nomentioning
confidence: 99%
See 1 more Smart Citation